Cinematic Histospheres On the Theory and Practice of Historical Films - Greiner, Rasmus (Springer Nature, 2021)
In this Open Access book, film scholar Rasmus Greiner develops a theoretical model for the concept of the histosphere to refer to the "sphere" of a cinematically modelled, physically experienceable historical world. His analysis of practices of modelling and perceiving, immersion and empathy, experience and remembering, appropriation and refiguration, combine approaches from film studies, such as Vivian Sobchack's phenomenology of film experience, with historiographic theories, such as Frank R. Ankersmit's concept of historical experience. Building on this analysis, Greiner examines the spatial and temporal organization of historical films and presents discussions of mood and atmosphere, body and memory, and genre and historical consciousness. The analysis is based around three historical films, spanning six decades, that depict 1950s Germany: Helmut Käutner's Sky Without Stars (1955), Jutta Brückner's Years of Hunger (1980), and Sven Bohse's three-part TV series Ku'damm 56 (2016).